Análise da influência dos parâmetros tempo e temperatura na fundição de alumínio reciclado em forno resistivo a partir do planejamento fatorial - Freitas, Vivianne Rodrigues de (Universidade Federal Rural do Semi-Árido, 2017)
In view of the increased use of aluminum as raw material in the manufacture of packaging, the attempts of reutilization of these types of laminates has been growing and the increase in solid waste generation means that the recycling processes of this material are increasingly relevant to sustainable development. One of the processes used for the reuse of laminates from packaging is foundry. Such a process can be achieved in numerous types of furnaces. In muffle type electric resistive ovens it is carried out in a simple way, by inserting the values of times, gradients, heating ramps, and temperatures in the digital oven controller however as the variation of the parameters influences the result of the process, it may end up not reaching the best possible result, in this work the time and temperature parameters in the casting of recycled aluminum in furnaces of this type will be analyzed, the response surface modeling and contour curve, as well as the pareto graph used to analyze the influences of these parameters was implemented by Statistica software from Dell Inc. (2016), version 13, this analysis was based on the factorial design 22, with the analyzed parameters temperature and time, the first being the most significant variable for the casting process.
Keywords: Alumínio; Reciclagem; Fundição; Planejamento fatorial; Aluminum; Recycling; Foundry; Factorial planning; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA